2018
DOI: 10.1007/s13762-018-2155-3
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of agro-industrial effluents for polyhydroxyalkanoates production using Bacillus subtilis RS1

Abstract: The effectiveness of inexpensive agro-industrial wastes such as sugarcane molasses, paper mill effluent, and dairy effluent for the production of polyhydroxyalkanoates (PHAs) using Bacillus subtilis RS1 was assessed in this study. Laboratory-scale fermentations were carried out with both raw and pre-treated agro-industrial effluents, and maximum PHAs yield was observed in pre-treated effluents. Experimental variables such as pH, inoculum dose, and incubation time were further optimized to maximize PHAs yield, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 22 publications
1
11
0
3
Order By: Relevance
“…Otherwise, the production of PHA by the second group is not influenced by the supply of nutrients and is also able to continue to maintain PHA during its growth stage [ 49 ]. Nitshke et al reported that mutant strains of Azotobacter vinelandii , recombinant Escherichia coli and Alcaligenes latus are examples of the bacteria species that belong to this second group [ 50 ].…”
Section: Polyhydroxyalkanoate (Pha)mentioning
confidence: 99%
“…Otherwise, the production of PHA by the second group is not influenced by the supply of nutrients and is also able to continue to maintain PHA during its growth stage [ 49 ]. Nitshke et al reported that mutant strains of Azotobacter vinelandii , recombinant Escherichia coli and Alcaligenes latus are examples of the bacteria species that belong to this second group [ 50 ].…”
Section: Polyhydroxyalkanoate (Pha)mentioning
confidence: 99%
“…For that reason, many residues from different processes have been studied as potential culture media components. Among those, dairy effluents, molasses, paper mill effluents, winery wastewaters, food processing wastes, whey thin stillage, crude glycerol, and many others have been investigated (RATHIKA et al, 2018;KADIER et al, 2014;REVIN et al, 2018;SANTOS et al, 2016).…”
Section: Vinasse Management Challenges: Advantages Disadvantages Of Fertirrigation and Other Technological Opportunitiesmentioning
confidence: 99%
“…and Bacillus spp., for biosurfactant production (NASPOLINI et al, 2017;MD, 2012), Xanthomonas campestris for xanthan gum production (non-food applications) (BECKER et al, 1998), Bacillus spp. for bioplastic production (RATHIKA et al, 2018;DESOUKY et al, 2017), Acetobacter spp. and Gluconacetobacter spp.…”
Section: Vinasse Management Challenges: Advantages Disadvantages Of Fertirrigation and Other Technological Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, agro-industrial wastewater and sludge have also attracted great interest. A plethora of agro-industrial effluents have been tested as substrate for PHAs production: Sugarcane molasses, paper mill effluent, dairy effluent [20], distillery effluents [21], rice winery wastewater [22], and yeast industry wastewater [23]. Authors often agree in concluding that the reutilization of wastewater and sludge as a carbon substrate not only abates the cost of PHAs production [20,21] but also provides for a significant reduction of the sludge disposal cost [19], constituting a sustainable waste management [15,18] and significantly decreasing the environmental impact of PHAs [17].…”
Section: Introductionmentioning
confidence: 99%